THYROID DISEASE: A STUDY IN HIROSHIMA, JAPAN - HOLLINGSWORTH, DOROTHY R.; HAMILTON, HOWARD B.; TAMAGAKI, HIDEYA; BEEBE, GILBERT W. (Medicine (Baltimore), 1963)
The relation of thyroid disease to single, whole-body exposure to ionizing radiation was studied in matched samples of exposed and non-exposed subjects residing in Hiroshima, Japan. Clinical investigations were conducted on 169 patients with thyroid disease, of whom 152 were females. It was concluded that a number of etiological factors are significant in the production of simple goiter. Carcinoma of the thyroid was diagnosed in 12 patients. Although a greater number of malignancies were seen among the most heavily exposed, differences among distance groups was not statistically significant.